The Reproduction Trajectories of Institutions of Social Isolation of Individual Population Groups in the Regions of Russia - Berzin, Boris Yuryevich; Kuzmin, Aleksandr Ivanovich; Pyshmintseva, Olga Aleksandrovna (Economy of Regions, 2015)
The article deals with the spatial socio-demographic isolation as a factor of the current system of settlement in Russia’s regions. In theory, the phenomena of loneliness and social isolation have their demographic, socio-economic and psychological roots. Conceptually, they are expressed in the theories of nuclearization of family structure of society and the family’s loss of its core functions, deprivation of a person (of friends and relatives), in the paradigm of the second demographic transition. In fact, the trend towards the abandonment of birth, growth of cohabitations and divorces, premature mortality as the cause of widowhood are complemented by the institutional factors strengthening the foundations of a singular way of life, including various forms of isolation of an individual from the social environment in a post-industrial society. The main reasons of the socio-demographic isolation are following: the tendency of increasing a number of private households represented by lonely people, both elderly and young; as well as the prevalence of the institute of widowhood (mortality risks influencing the marriage and the family); the impact of flows of labour, academic, self-preservation, consumer migration (both returned and irretrievable types) on the reproduction of the population. Psychologically, the demographic isolation of certain local communities contributes to the feelings of loneliness as a regulator of the communication intensity and interaction between individuals. In the socioeconomic aspects, the isolation of local communities is associated with the factor of remote location of families from the centers of communication and real markets, with the development of new Russian and global logistics systems, with are deprivation of traditional sources of household income as a specific form of survival in the vast expanses of life of the Russian society.